posted by Bart on .
I know the answer to this question is: -1. I got that answer by substituting -1 in for x. Please show me how I should do this the correct way.
something wrong with my answer two hours ago? Here it is again.
x/(3x+6) - (x+1)/(3x-6) = 1/(x^2-4)
factor out the 1/3 on the left side, and factor the right side
1/3 (x/(x+2) - (x+1)/(x-2)) = 1/((x+2)(x-2))
now put LS over a common denominator
1/3 (x(x-2) - (x+1)(x+2))/((x-2)(x+2)) = 1/((x+2)(x-2))
multiply through by 3(x-2)(x+2)
x(x-2) - (x+1)(x+2) = 3
x^2 - 2x - x^2 - 3x - 2 = 3
-5x - 2 = 3
-5x = 5
x = 1
Steve, thank you for showing me again. Yes, I couldn't quite get it last time. I understood factoring out the 1/3 on the left side. I understood factoring the denominator on the right side. After that I have trouble. Could you please show it to me again with more steps in place?